2016
DOI: 10.1103/physrevb.93.161102
|View full text |Cite
|
Sign up to set email alerts
|

Shifted-action expansion and applicability of dressed diagrammatic schemes

Abstract: While bare diagrammatic series are merely Taylor expansions in powers of interaction strength, dressed diagrammatic series, built on fully or partially dressed lines and vertices, are usually constructed by reordering the bare diagrams, which is an a priori unjustified manipulation, and can even lead to convergence to an unphysical result [Kozik, Ferrero, and Georges, PRL 114, 156402 (2015)]. Here we show that for a broad class of partially dressed diagrammatic schemes, there exists an action S (ξ) depending a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 20 publications
1
88
0
Order By: Relevance
“…Also, very recent studies have shown that self-consistent Φ-derivable approximations can converge to unphysical solutions; [34][35][36][37][38][39][40][41][42][43][44]47,48 similar issues have been noted in the context of time-dependent simulations [40][41][42][43][44][47][48][49] using the Kadanoff-Baym equations, but can be remedied by introducing self-consistent contributions in controlled fashion. 43 Nevertheless, the use of self-consistent MBPT may be justified to some extent.…”
Section: 23mentioning
confidence: 97%
“…Also, very recent studies have shown that self-consistent Φ-derivable approximations can converge to unphysical solutions; [34][35][36][37][38][39][40][41][42][43][44]47,48 similar issues have been noted in the context of time-dependent simulations [40][41][42][43][44][47][48][49] using the Kadanoff-Baym equations, but can be remedied by introducing self-consistent contributions in controlled fashion. 43 Nevertheless, the use of self-consistent MBPT may be justified to some extent.…”
Section: 23mentioning
confidence: 97%
“…First specific reports about unexpected theoretical consequences induced by the breakdown of the many-body perturbation expansion have been recently presented by several groups. Such effects range from the occurrence [24][25][26][27] of low-frequency divergences of two-particle irreducible vertex functions in the Hubbard 28 and Falicov-Kimball 29 models to the multivaluedness [30][31][32][33][34][35][36] of the electronic self-energy expressed as a functional of the (interacting) Green's function or, equivalently, of the Luttinger-Ward functional. All these manifestations of non-perturbativeness are interconnected and represent different aspects of the same problem, as suggested in some of the abovementioned works.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we note that it is possible to generalize the method to more general diagrammatic schemes by the use of a shifted action [26], where one has to consider additional interaction vertices that act as counterterms.…”
mentioning
confidence: 99%
“…All our error bars correspond to one standard deviation. We resum all bare tadpoles diagrams, whose effect is to shift the chemical potential µ(U ) = µ 0 + U n 0 /2, where µ 0 is the chemical potential needed to get the density n 0 in the absence of interactions (this corresponds to the first-order semi-bold scheme introduced in [26]). This is useful because one has a smaller density shift as a function of U .…”
mentioning
confidence: 99%